2000
DOI: 10.22358/jafs/68045/2000
|View full text |Cite
|
Sign up to set email alerts
|

The effect of supplementing rations with selenium and vitamin E on biochemical parameters in blood and performance of cows in the early stage of lactation

Abstract: Thirty-two cows (Black-and-White x HF) in the first 100 days of lactation were divided into 4 groups and fed rations composed of equal proportions of roughages and concentrates in amount of 1 kg per 2 kg of milk at yield exceeding 12 kg/day. The concentrates were supplemented with vitamin E (group I, 336 mg; groups II, III, and IV, 672 mg/cow/day) and selenium: group I, no supplementation; group II, 4 mg/cow/day as sodium selenite; group III, 4 mg/cow/day as selenium yeast; group IV, 2 mg/cow/day as selenium y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
2
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
4
2
0
Order By: Relevance
“…These observations are in line with those of Van Ryssen et al (1989) in sheep, Falkowska et al (2000) and Gunter et al (2003) in cows, Ortman and Pehrson (1999) in dairy cows and Pechova et al (2012) in goats, who reported higher whole blood Se concentrations in animals supplemented with organic Se compared to those administered diets of a comparable Se content where sodium selenite was the source of supplementary Se.…”
Section: Selenium In Bloodsupporting
confidence: 90%
“…These observations are in line with those of Van Ryssen et al (1989) in sheep, Falkowska et al (2000) and Gunter et al (2003) in cows, Ortman and Pehrson (1999) in dairy cows and Pechova et al (2012) in goats, who reported higher whole blood Se concentrations in animals supplemented with organic Se compared to those administered diets of a comparable Se content where sodium selenite was the source of supplementary Se.…”
Section: Selenium In Bloodsupporting
confidence: 90%
“…Our findings demonstrated insignificant alterations of serum triacylglycerol, HDL, LDL levels in supplemented ewes compared with the control group. These findings were in line with that recorded by NEMAT (2015) and being away from that reported by others (FALKOWSKA et al 2000;SHERIEF et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Also, the insignificant effect of treatment with Se or Se+Vit. E on triglycerides was in accordance with the previous work on cows, sheep, lambs or goats by Shinde et al (2009), Soliman et al (2012), Falkowska et al (2000, Antunović et al (2014) andZiaei, (2015) who reported that selenium supplementation had no significant effect on blood triglycerides.…”
Section: Plasma Total Cholesterol and Triglyceridessupporting
confidence: 91%